Development of Kodular Application-Based Interactive Learning Media in Engineering Mechanics I Course - Simbolon, Krisdayanti Siska Oktavia; Silalahi, Juniman (CIVED, 2023)
This study is set by the absence of kodular-based learning media at Padang State University, especially in Engineering Mechanics I course. With the passage of time, the learning media which are utilized on learning must be innovated and provide new experiences to students so that this research problem can be defined. The validity and practicality of kodular application-based interactive learning media in Engineering Mechanics I course. This study goals are to determine the validity and practicality of kodular-based interactive learning media in Engineering Mechanics I course. This research applies Research and Development (R&D) research types and apply the 4D development model. The results of this development state that the rate of validity of interactive learning media based on kodular applications in the Engineering Mechanics I course depends on the assessment of the Expert Appraisal is highly valid. The rate of practicality is depending on the outcome of questionnaires from PTB FT UNP students’ class of 2022, eminently practical to be used by students in Engineering Mechanics I learning.